Design Of Pop-Up Letters Card Media Based On Edutainment For Dyslexic Children In Elementary School - Nisrina Haifa; Syarif Hidayat; Sima Mulyadi (International Journal Labs, 2024)
This research focuses on the development based on edutainment pop-up letter card media customized for use by dyslexic children in elementary school. Dyslexia poses significant challenges for children in learning to read and write, requiring specialized educational tools to support their learning needs. The developed pop-up letter cards integrate visual, auditory, and tactile elements to create an engaging and multisensory learning experience. By leveraging interactive features and user-friendly design, it is hoped that the development of this media can provide a solution to reading difficulties for dyslexic students in elementary school. The method used in this research is Design Based Research (DBR), the selection of this method is considered appropriate for developing a product that can be one of the solutions to the problems that occur in the field.